(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The integration of digital educational technologies in teaching mathematics is transforming traditional instructional approaches. This paper explores how digital tools enhance student engagement, foster analytical skills, and provide individualized learning pathways. The study focuses on the applicability of these technologies in the pedagogical context, particularly for students in teacher education programs, highlighting their potential to improve both teaching methods and learning outcomes.